2014
DOI: 10.1007/s13187-014-0732-9
|View full text |Cite
|
Sign up to set email alerts
|

Medical Advocacy and Supportive Environments for African-Americans Following Abnormal Mammograms

Abstract: African American women experience disproportionately adverse outcomes relative to non-Latina White women after an abnormal mammogram result. Research has suggested medical advocacy and staff support may improve outcomes among this population. The purpose of the study was to understand reasons African American women believe medical advocacy to be important and examine if and how staff can encourage and be supportive of medical advocacy. A convenience-based sample of 30–74 year old women who self-identified as A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Some studies have shown that Black women are less likely to self-advocate during a medical encounter, 33 whereas others have found that increased self-advocacy by Black women is associated with better outcomes. 34,35 These prior studies frame self-advocacy behaviors positively, as an effective strategy on the individual level to improve outcomes and reduce health inequities. 34 In contrast, our findings suggest that selfprotective behaviors are reactive, adaptive survival strategies in the face of persistent cultural and structural racism.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown that Black women are less likely to self-advocate during a medical encounter, 33 whereas others have found that increased self-advocacy by Black women is associated with better outcomes. 34,35 These prior studies frame self-advocacy behaviors positively, as an effective strategy on the individual level to improve outcomes and reduce health inequities. 34 In contrast, our findings suggest that selfprotective behaviors are reactive, adaptive survival strategies in the face of persistent cultural and structural racism.…”
Section: Discussionmentioning
confidence: 99%
“…[27][28][29][30][31][32][33][34] Patient navigation has been successful in gaining appropriate follow-up and shortening time following abnormal mammograms. 3,32,35,36 Although patient navigation programs are a strategy to address mammogram process barriers, particularly for vulnerable women, [35][36][37][38][39][40] these programs can be costly and require additional trained personnel. While the safety-net facility was the only facility in our study that had an established patient navigator program, some women in the safety-net facility still experienced delays to follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…This study combines data from two projects conducted between February 2012 and July 2013 (Mujeres Poderosas/Powerful Women (MPPW) - Molina, Hohl et al, 2014, Molina, Beresford, et al, 2014; Sisters-Healing-Advocating-Praising-Empowering-Sisters (SHAPES) - Molina, Hempstead et al, 2015). Staff recruited women from the Puget Sound area, wherein African American and Latina residents represent respectively 8% and 6% of the population (WA Department of Public Health, 2013) and exhibit breast cancer disparities that mirror those observed at a national level (Adams et al, 2009; Arnsberger et al, 2006; Press et al, 2008; Ramirez et al, 2013).…”
Section: Methodsmentioning
confidence: 99%